Hubungan Tingkat Pengetahuan Kesehatan Reproduksi dengan Kesiapan Menghadapi Masa Pubertas pada Siswi Sekolah Dasar - Pinkan Ameliy; Sri Kustiyati (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Puberty is a transitional period characterized by physical, mental, and emotional changes. Knowledge of reproductive health is essential to help female students prepare for these changes. This study aimed to determine the relationship between the level of reproductive health knowledge and preparedness for puberty among female students at SDIT Ar-Risalah Wonosari, Klaten. This research employed a correlational analytic design with a cross-sectional approach. The study population consisted of 57 fourth- and fifth-grade female students, with a sample of 53 students who met the inclusion criteria and were selected using a total sampling technique. Data were collected using a questionnaire and analyzed with the Chi-square test. The majority of respondents had a good level of reproductive health knowledge (38 students, 71.7%) and were prepared to face puberty (34 students, 64.2%). The Chi-square test showed a significant relationship between the level of reproductive health knowledge and preparedness for puberty (p = 0.002), with a moderate strength of association based on Cramer's V value of 0.492. In conclusion, there was a significant relationship between the level of reproductive health knowledge and preparedness for puberty among female students at SDIT Ar-Risalah Wonosari, Klaten.